Description of Knowledge About Dental Calculus Using Rolling Ball Media Among Dasawisma Cadres in Sidobecik Hamlet, Pulorejo Village in 2025 - Setyo, Eunike Meydi Putri Cahya Ratuning; Hadi, Sunomo; Larasati, Ratih (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Dental calculus is a thick, yellow hard layer attached to the teeth caused by leftover food debris that is not cleaned properly. If left untreated, dental calculus can lead to periodontal tissue problems such as gingivitis, periodontitis, loose teeth, and bad breath. Dental calculus can be prevented by maintaining oral health, including preventive actions like tooth brushing and scaling treatment. This study aims to describe the knowledge about dental calculus using rolling ball media among Dasawisma cadres in Sidobecik Hamlet, Pulorejo Village. This descriptive study used a questionnaire method involving 40 Dasawisma cadres as respondents. Data were collected to assess knowledge about the definition, causes, effects, and ways to overcome dental calculus. Data analysis was conducted by calculating respondents’ answers and converting them into percentages to categorize knowledge levels. The results showed that after the education session, the average knowledge about the definition, causes, effects, and management of dental calculus using rolling ball media among Dasawisma cadres was 89%, categorized as good